Cujo [videorecording (Blu-Ray)] - King, Stephen (Kino Lorber, 2023)
In rural Castle Rock, Maine, Vic and Donna Trenton struggle to repair their crumbling marriage, while their young son Tad befriends a hulking, lovable, 200-pound St. Bernard named Cujo. With Vic away on business, Donna and Tad take their decrepit car to be fixed at the remote farm of their mechanic. As their aging Pinto sputters to a stop and dies, Cujo appears. But the once docile dog has undergone a hideous transformation and becomes a slavering, demonic killer possessed by almost supernatural strength...and unholy cunning. So get ready for Cujo, an irresistible movie force from the King of Horror.